Valorization of Eucalyptus urograndis lignin: mechanistic approaches of different delignification methods and chemical modifications via sustainable methodology - Oliveira, Davi Rabelo de (2025)
Lignin, a complex and abundant aromatic biopolymer, represents a renewable resource that is still underutilized in the concept of biorefineries. The effective valorization of lignin depends critically on its chemical structure, which is strongly influenced by the extraction method employed, and on chemical modifications that modulate its properties for specific applications. However, traditional extraction methods can lead to altered structures, and chemical modifications often involve dangerous reagents and long reaction times. This thesis had the following two objectives: (1) to comparatively investigate the impact of the Kraft, Rapid Pyrolysis (FP) and Microwave-Assisted Organosolv (MWAOD) delignification methods on the structural, thermal and antioxidant characteristics of Eucalyptus urograndis lignin, using Milled Wood Lignin (MWL) as a reference; and (2) to develop and evaluate a sustainable and selective acetylation method for Kraft lignin, employing acetic acid as a reagent under microwave irradiation. The lignins were extensively characterized by FTIR, NMR (2D HSQC, ³¹P), GPC, TGA, DSC, and antioxidant activity assay (DPPH). The results of delignification revealed that the methods produced lignins with varying yields (33-69%), and high purities (76-93%). The severity of the process (FP>Kraft>MWAOD) has been shown to directly influence the structure of the lignin, resulting in lower molecular weights (657-1959 g/mol), higher degree of condensation (β-5', 5-5' bonds) and higher content of phenolic hydroxyls, with consequent changes in thermal properties and antioxidant capacity. The modification study demonstrated that microwave-assisted acetylation with acetic acid is a fast and efficient alternative, allowing partial and selective acetylation (preferably in phenolic hydroxyls) of Kraft lignin, modifying its solubility, thermal stability and antioxidant activity in a controlled manner. With the results obtained, it was possible to conclude that the selection of the extraction method is fundamental to define the properties of technical lignin and that innovative and sustainable modification approaches, such as microwave acetylation with acetic acid, are promising to adapt lignin to higher value-added applications, contributing to the circular economy and the development of biorefineries.